2008
DOI: 10.1143/jjap.47.914
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Compression of Gaussian Pulse from Annular Aperture in Far-Field

Abstract: The far-field spectral characteristics of a time-dependent Gaussian pulse diffracted by a circular aperture with a central obstruction (annular-aperture) are studied both theoretically and numerically. It was shown that the central obstruction causes diffracted spectrum compression, which can be compared with the normal circular aperture (without a central obstruction) without this effect. Also, the diffracted spectral intensity distributions with red and blue shifts of the maximum are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Spatio-temporal couplings of ultrashort pulses have come to play ever increasing-both desirable and undesirable-roles in important applications, including pulse compression, shaping, imaging, and focusing (see e.g. [1][2][3] and references therein). The propagation of an ultrashort pulse exposes it to many such distortions, of which some remain rather surprising.…”
Section: Introductionmentioning
confidence: 99%
“…Spatio-temporal couplings of ultrashort pulses have come to play ever increasing-both desirable and undesirable-roles in important applications, including pulse compression, shaping, imaging, and focusing (see e.g. [1][2][3] and references therein). The propagation of an ultrashort pulse exposes it to many such distortions, of which some remain rather surprising.…”
Section: Introductionmentioning
confidence: 99%
“…Many different kinds of behavior can exist around singular points, e.g., wave front dislocations, optical vortices, 3) spectral switches, and spectra distortions. [4][5][6][7][8][9][10][11][12] Most earlier publications used monochromatic waves as light sources [1][2][3] to discuss this singular behavior. In more recent studies, it has been found that, for polychromatic light 4,8) or broad-band short pulse wave fields 5,6) drastic spectral changes can also be exhibited.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Most earlier publications used monochromatic waves as light sources [1][2][3] to discuss this singular behavior. In more recent studies, it has been found that, for polychromatic light 4,8) or broad-band short pulse wave fields 5,6) drastic spectral changes can also be exhibited. These spectral changes are then analyzed and shown to be related to the spatial correlation of the light sources 12) (correlation-induced spectral changes) and/or with the limiting aperture [4][5][6][7][8] (aperture-induced spectral changes).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations